1-Methylxanthine enhances memory and neurotransmitter levels - Jäger, Ralf; Abou Sawan, Sidney; Orrú, Marco; Tinlsey, Grant M.; Purpura, Martin; Wells, Shawn D.; Liao, Kylin; Godavarthi, Ashok (PLOS ONE, 2025)
1-Methylxanthine (1-MX) is the major metabolite of caffeine and paraxanthine and might contribute to their activity. 1-MX is an adenosine receptor antagonist and increases the release and survivability of neurotransmitters; however, no study has addressed the potential physiological effects of 1-MX ingestion. The aim of this study was to compare the effect of 1-MX on memory and related biomarkers in rats compared to control. Memory (escape latency in the Morris water maze test), neurotransmitters (acetylcholine, dopamine, gamma-amino butyric acid (GABA)), and neurochemicals (BDNF, catalase, glutathione, Amyloid Beta and cyclic GMP) were analyzed from whole brain samples in young (8-weeks-old) and aged (16-months-old) rats following 12 days of supplementation (100 mg/d HED of 1-MX [UPLEVEL®, Ingenious Ingredients L.P., Lewisville, TX, USA]) via oral gavage. 1-MX supplementation reduced escape latency by 39% in young animals and 27% in aged animals compared to controls (both p<0.001). Additionally, 1-MX increased the levels of acetylcholine, dopamine, GABA, and cyclic GMP (all p<0.001). Furthermore, 1-MX supplementation led to reduced amyloid beta and higher catalase, BDNF and glutathione concentrations (p<0.001). Collectively, our findings suggest that 1-MX may have cognitive-enhancing and neuroprotective properties.